Obstructive Sleep Apnea Patients’ Compliance with Treatment of Continuous Positive Airway Pressure: A Literature Review - Borriboon , Chestharid; Chaiard, Jindarat; Tachaudomdach, Chiraporn (Journal of Thailand Nursing and Midwifery Council, 2021)
Obstructive sleep apnea (OSA) is a disorder caused by constriction of the upper respiratory tract during sleep, resulting in hypoxia and sleep disturbances. Obstructive sleep apnea requires specifc treatment using continuous positive airway pressure (CPAP), which is a high-effcacy standard method of treatment. To obtain maximum beneft of the CPAP treatment, the patient’s compliance is an essential factor. However, it is presently found that OSA patients’ compliance with this method of treatment is at a relatively low level. Causes of this could vary from physiological factors, such as sex, age, and symptomatic severity, which are immutable, to psychosocial and cognitive factors, such as perception of susceptibility, severity, benefts, self-effcacy, and obstacles, which are adjustable or ameliorable. This article primarily attempts to increase nurses’ or healthcare professionals’ understanding of factors related to patients’ compliance with the treatment. With such factors properly managed, treatment compliance can be promoted, which could reduce complications and expenses to be incurred. Accordingly, nurses are advised to conduct regular assessments of the CPAP machine, make regular enquiries about the patients’ problems and obstacles in using the machine, and promote the patients’ self-effcacy in using the CPAP machine, to encourage the patients’ compliance with the treatment method.